Prevalence of Extended-Spectrum Beta-Lactamase-Producing Escherichia Coli in Broiler Farms: A Systematic Review and Meta-Analysis - Phirum Or; Sukolrat Boonyayatra; Veerasak Punyapornwithaya; Nattakarn Awaiwanont (Veterinary Integrative Sciences)
Extended-spectrum beta-lactamases-producing Escherichia coli (ESBL E. coli) is a serious public health issue. ESBL E. coli in broiler production is known as potential risk for humans. This study aims to estimate the global pooled prevalence of ESBL E. coli in broiler farms. Literature searches were done via PubMed, Web of Science and Scopus. A random effect model was used to estimate the pooled prevalence. Heterogeneity was assessed by Cochrans’s Q test and I squared statistic (I2). Subgroup analysis and meta-regression was conducted to investigate the source of heterogeneity. Sensitivity and publication bias analyses were performed. Overall, 872 and 18 additional studies were retrieved from databases and bibliography searches. Thirty-seven studies met the inclusion criteria. Pooled prevalence of ESBL E. coli in broiler farms was 26.6% (95% CI = 18.2 to 37.3) and revealed high heterogeneity (Q = 1958.87 and I2 = 98.2%). The pooled prevalence of ESBL E. coli in broiler farms was almost identical between Asia; 33.0% (95% CI = 18.7 to 51.3) and Europe; 32.8% (95% CI = 15.0 to 57.4), while Africa showed the lowest at 12.4% (95% CI = 5.1 to 27.1). Prevalence of ESBL E. coli was found highest in fecal sources; 33.0% (95% CI = 21.5 to 46.8) followed by environmental sources; 28.3% (95% CI = 13.5 to 50.1) and other sources; 11.0% (95% CI = 5.0 to 22.8). Results from our study indicated moderate prevalence of ESBL E. coli in broiler farms globally and it has been fluctuating inconsistently in the last decade.